2013
DOI: 10.1007/s10936-013-9245-7
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Richness in Maternal Input and Vocabulary Development of Turkish Preschoolers in the Netherlands

Abstract: The present study examined lexical richness in maternal input to Turkish preschool children in the Netherlands and the relationship with their vocabulary. Fifteen Turkish mother-child dyads were videotaped at the age of 3 and 4 in three settings: book reading, picture description and block building. Children's vocabulary in Turkish was measured at the age of 3 and 4 and in Dutch at the age of 5;10. The lexical richness of the input was analysed both quantitatively (tokens) and qualitatively on diversity, densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
2
12
0
1
Order By: Relevance
“…Traditionally, in child language research, lexical diversity has been measured using a type-token ratio (TTR). However, because TTR seems to be dependent on the total number of tokens produced (Rietveld & van Hout, 1993;van Hout & Vermeer, 1988), other means of measuring lexical diversity were designed, including Guiraud's index (Guiraud, 1954) and the D index (Demir-Vegter, Aarts, & Kurvers, 2014;Malvern & Richards, 2002). As objections have been raised against all the available measures, we used the most straightforward measure for lexical diversity-the number of word types used in a standardized time frame (see also Huttenlocher et al, 2010;Rowe, 2012).…”
Section: Lexical Diversitymentioning
confidence: 99%
“…Traditionally, in child language research, lexical diversity has been measured using a type-token ratio (TTR). However, because TTR seems to be dependent on the total number of tokens produced (Rietveld & van Hout, 1993;van Hout & Vermeer, 1988), other means of measuring lexical diversity were designed, including Guiraud's index (Guiraud, 1954) and the D index (Demir-Vegter, Aarts, & Kurvers, 2014;Malvern & Richards, 2002). As objections have been raised against all the available measures, we used the most straightforward measure for lexical diversity-the number of word types used in a standardized time frame (see also Huttenlocher et al, 2010;Rowe, 2012).…”
Section: Lexical Diversitymentioning
confidence: 99%
“…However, the metric that is used most often, and which produces the most consistent effects, is lexical diversity, operationalized as the number of different word types produced by the caregiver during a set timeframe (e.g. Bornstein et al, 1998;Demir-Vegter, Aarts, & Kurvers, 2014;Hoff & Naigles, 2002;Huttenlocher et al, 2010;Pan, Rowe, Singer, & Snow, 2005;Rowe, 2012; see also Hsu, Hadley, & Rispoli, 2015, for results for verb lexical diversity). For example, Bornstein et al (1998) found that both maternal lexical diversity and maternal MLU were significant predictors of child vocabulary at 18 months in a structural equation model.…”
Section: Introductionmentioning
confidence: 99%
“…A key message in UK preschool educational settings is to maximise the exposure that children have to language (Bercow, 2008;Social Mobility Commission, 2017), and numerous studies have shown that quantity of children's oral language exposure (the sheer amount of language input) relates to their vocabulary size (Bornstein, Haynes, & Painter, 1998;Bornstein & Tamis-LeMonda, 1995;Cartmill et al, 2013;Hart & Risley, 1992Hoff & Naigles, 2002;Hurtado, Marchman, & Fernald, 2008;Huttenlocher, Haight, Bryk, Seltzer, & Lyons, 1991;Huttenlocher, Waterfall, Vasilyeva, Vevea, & Hedges, 2010;Kamil & Hiebert, 2005;Pearson, Fernandez, Lewede, & Oller, 1997;Rowe, 2012). The lexical diversity, or the range of vocabulary, of speech to children has also been assessed against children's language development (Bornstein et al, 1998;Demir-Vegter, Aarts, & Kurvers, 2014;Hoff & Naigles, 2002;Huttenlocher et al, 2010;Pan, Rowe, Singer, & Snow, 2005;Rowe, 2012).…”
mentioning
confidence: 99%